Biossegurança no laboratório - ISHAK, Ricardo (2014)
The occurrence of laboratory-acquired infections have elicited in the last ten years an intense interest in methods and procedures for the safe handling of microbiological material. The major laboratory safety problem is aerial transmission, however, protection against airborne hazards is efficiently achieved by the use of microbiological safety cabinets. Biosafety rules should be strictly followed by all members of a laboratory. Evaluation of these procedures should be effectively performed by an independent biosafety committee. The/ upsurge of AIDS should stimulate the adoption of safe working procedures in the laboratory.